Pengaruh Pendidikan Kesehatan Terhadap Kepatuhan Diet Pada Pasien DM Tipe 2 di Irna Non Bedah Penyakit Dalam RSUP dr.m. Djamil Padang Tahun 2014 - Hendra Harwadi; Kusman Ibrahim; Helmi Hayaty (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
Diabetes Mellitus is a degenerative disease that has become a health problem in the world. The prevalence of this disease is increasing in developing countries, including Indonesia. Uncontrolled blood sugar and further complications may be influenced by the patient's behavior and lifestyle. Disobedience in implementing the diet is one of the problems for Diabetic patients. One of the nursing interventions that can be used to overcome the disobedience of the diet is to provide health education on dietary management. The purpose of this study was to determine the effect of health education on dietary obedience in patients with Diabetes Mellitus in Irna Non Bedah Penyakit Dalam, Dr. M. Djamil Hospital. The type of research is a Quasi-Experimental by using One Group Pre-Post Test Design, 15 people as samples were taken by Purposive Sampling Method. Data collection was conducted on 01 February 2014 to 05th March 2014. The statistical test used is Wilcoxon signed rank test. The results show that there is an increased obedience of patients in implementing Diabetic diet (the right amount, the right type, and the right schedule) after a given health education (p = 0.002). As a conclusion, giving the health education about the implementation of the diet can improve dietaryobedience in patients with Diabetes Mellitus who are undergoing treatment. It is expected that the implementation of health education can be done intensively in health services in Dr. M. Djamil Hospital as anticipation of further complications due to disobedience in implementing the diet.